2021
DOI: 10.1002/lipd.12316
|View full text |Cite
|
Sign up to set email alerts
|

Growth and fatty acid composition of Acutodesmus obliquus under different light spectra and temperatures

Abstract: The combined impact of temperature and light spectra on the fatty acid (FA) composition in microalgae has been sparsely investigated. The aim of this study was to investigate the interactions of light and temperature on the FA composition in Acutodesmus obliquus. For this purpose, A. obliquus was cultivated with different temperatures (20, 30, and 35 C), as well as broad light spectra (blue, green, and red light). Growth and FA composition were monitored daily. Microalgal FA were extracted, and a qualitative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 59 publications
(93 reference statements)
6
34
1
Order By: Relevance
“…It was shown that wavelengths below 500 nm combined with red light (600-700 nm) lead to higher photosynthetic efficiency and growth in A. obliquus, compared to monochromatic red light (600-700 nm) (Osterthun, Helamieh, et al, 2021). The FA composition is in accordance with several published data on the same microalgal strain (Abomohra et al, 2013;Helamieh et al, 2021). However, due to the lower cultivation temperature, a higher relative percentage of PUFA, such as 18:3 and 16:4 was observed in this study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It was shown that wavelengths below 500 nm combined with red light (600-700 nm) lead to higher photosynthetic efficiency and growth in A. obliquus, compared to monochromatic red light (600-700 nm) (Osterthun, Helamieh, et al, 2021). The FA composition is in accordance with several published data on the same microalgal strain (Abomohra et al, 2013;Helamieh et al, 2021). However, due to the lower cultivation temperature, a higher relative percentage of PUFA, such as 18:3 and 16:4 was observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…The elevation of the FA16:1 in the heterotrophic dark treated samples is remarkable, even though no immediate explanation for it can be found in the literature. In addition, different from (Helamieh et al, 2021), no impact of the light conditions on the relative percentage of 18:4 in A. obliquus was observed (data not shown).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations